Interaction of Age and Self-reported Physical Sports Activity on White Matter Hyperintensity Volume in Healthy Older Adults - Franchetti, Mary Kathryn; Bharadwaj, Pradyumna K.; Nguyen, Lauren A.; Van Etten, Emily J.; Klimentidis, Yann C.; Hishaw, Georg A.; Trouard, Theodore P.; Raichlen, David A.; Alexander, Gene E. (Frontiers in Aging Neuroscience, 2020)
Cerebral white matter lesion load, as measured by white matter hyperintensity (WMH) volume with magnetic resonance imaging, has been associated with increasing age and cardiovascular risk factors, like hypertension. Physical sport activity (PSA) may play an important role in maintaining white matter in the context of healthy aging. In 196 healthy older adults, we investigated whether participants reporting high levels of PSA (n = 36) had reduced total and regional WMH volumes compared to those reporting low levels of PSA (n = 160). Age group [young-old (YO) = 50-69 years; old-old (OO) = 70-89 years], PSA group, and age by PSA group interaction effects were tested, with sex, hypertension, and body mass index as covariates. We found significant main effects for age group and age by PSA group interactions for total, frontal, temporal, and parietal WMH volumes. There were no main effects of PSA group on WMH volumes. The OO group with low PSA had greater total, frontal, temporal, and parietal WMH volumes than the YO with low PSA and OO with high PSA groups. WMH volumes for the YO and OO groups with high PSA were comparable. These findings indicate an age group difference in those with low PSA, with greater WMH volumes in older adults, which was not observed in those with high PSA. The results suggest that engaging in high levels of PSA may be an important lifestyle factor that can help to diminish WMH lesion load in old age, potentially reducing the impact of brain aging.